Régulation, verrous technologiques et transition écologique : le cas des formaldéhydes - Nicolas Béfort (Revue de la Régulation)
The present change towards the use of renewable resources is activating production regimes in which economic actors are trying to use as an opportunity the social contestation of toxic molecules. In this context, our aim is to analyze the use of formaldehyde, an emblematic and carcinogenic molecule widely used in the production of resins and adhesives.Starting with a review of the regulation literature analyzing innovation, we discuss here the 'evolutionist theory of environmental innovations' in order to highlight an analytical framework that aims to analyze from a historical perspective the dynamics of acquiring knowledge. This method takes into account both the conflicts and the different institutions involved in the process of change of regimes of knowledge accumulation and economic activities. It brings to highlight historical dynamics, which does not radically change the products, even with new inputs.